Dual lithium storage of Pt electrode: alloying and reversible surface layer. Issue 34 (18th August 2021) - Kim, Yunok; Choi, Woosung; Kim, Ok-Hee; Park, Hyunyoung; Yun, Soyeong; Thangavel, Ranjith; Cho, Yong-Hun; Yoon, Won-Sub
Abstract : As the importance of additional capacity beyond the theoretical limitation of lithium-ion batteries has been recognized, extensive research into effectively utilizing the extra lithium accommodation is being conducted. Abstract : As the importance of additional capacity beyond the theoretical limitation of lithium-ion batteries has been recognized, extensive research into effectively utilizing the extra lithium accommodation is being conducted. One of the most effective strategies to increase capacity is the use of catalytic materials well-known to promote electrochemical reactivity. Herein, we adopt platinum (Pt) metal as an electrode material to take advantage of dual charge storage properties: (i) the Li–Pt alloying reaction and (ii) additional Li storage reaction induced by catalytic properties. The prepared Pt electrode yields an initial capacity of ∼863 mA h g −1 during the 1 st cycle and a reversible capacity of ∼600 mA h g −1, which is much larger compared to the previously reported capacity of 137 mA h g −1 . Additionally, the complex Li-ion storage in Pt metal involving alloying reaction and catalytic effect induced charge storage reactions shows high reversibility, realizing a stable electrochemical performance upon cycling. This study holds great promise for understanding the origin of additional capacities from the catalytic effect of alloying type anodes and could be a trendsetter for designing high-capacity anode materials for next-generation lithium rechargeable batteries.